Organic carbon accumulation in the equatorial Atlantic - Wagner, Thomas (Supplement to: Wagner, T (2000): Control of organic carbon accumulation in the late Quaternary Equatorial Atlantic (ODP Sites 664, 663): productivity versus terrigenous supply. Paleoceanography, 15(2), 181-199, https://doi.org/10.1029/1999PA000406, 2000)
Organic geochemical records of the last 940 kyr are presented for equatorial Atlantic Ocean Drilling Program (ODP) sites 663 and 664 and discussed with regard to the development of ocean productivity and African paleoclimate. Proportions of marine and terrigenous organic matter (OM) are estimated from elemental, pyrolytic, isotopic, and petrologic data. Spectral analyses reveal a strong power at the eccentricity and obliquity band, indicating a close response of tropical organic sedimentation to the climatic evolution at high latitudes. The orbital covariance of organic carbon with biogenous opal and terrigenous records favor that glacially enhanced dust supply and surface water mixing were primary controls for deposition of organic carbon. Wind-borne supply of terrigenous OM contributes 26 to 55% and 0 to 39% to the bulk OM based on microscopic and isotopic records, respectively. Admixture of C4 plant matter was approximated to contribute up to 16% to the bulk organic fraction during peak glacial conditions.